Capacitive tip loaded linearly tapered meander line antenna for UHF RFID tag applications - Bhaskar S.; Singh A.K. (My University, 2025)
This paper proposes a novel and simple antenna for Radio Frequency Identification (RFID) tags at UHF band (915 MHz). The proposed antenna is made up of linearly tapered meander line, T-match network and two rectangular sections at the end of radiating body. Overall dimension of the antenna is 50×22 mm2. It has 10.36 m maximum read range with omnidirectional radiation pattern at 915 MHz. Experimental results validates the simulated results. © 2017 IEEE.